Information technology in disaster risk reduction : second IFIP TC 5 DCITDRR International Conference, ITDRR 2017, Sofia, Bulgaria, October 25-27, 2017, Revised selected papers /: second IFIP TC 5 DCITDRR International Conference, ITDRR 2017, Sofia, Bulgaria, October 25-27, 2017, Revised selected papers. (2019) - Unknown
No abstract available